Hand Crafted Plates / Muhammad Arif Mohd Mukhidin - Muhammad Arif, Mohd Mukhidin (2020)
• Business concepts Clay Craft one of the company will come out the product made by clay. The designers in this company will create the new design for the plates, bowls, teapot, cup and also bakery stuff. Our products are very recommended to everyone because it is very long-lasting product. Even the price are bit expensive and very worth it with the products. Our products be expensive because the design are hand craft and the material used very high-end. • Products or services being offered The products can get at the Clay Craft store in Kuala Lumpur. Our products also can get from the website and our company will deliver the order home to home. The promotion sale depends on festival celebration, new year, Merdeka sale and etc. • Market potential/ Target market Clay craft products made by hand craft and very attractive design. The target market for working people men and women age around 25 years old and above. The customers leave in Kuala Lumpur area. The food and beverage industry such as the restaurant, café, hotel and food court. • Competitive advantage Clay Craft products made from clay. The products very long-lasting. The surface are non-stick and easy to wash. The design are hand crafted and look very attractive. The products heat resistant available for steamer, microwave, oven and etc • The profitability Sales are an important factor in determining profitability. The return on sales ratio measures profits after taxes based upon the current year's sales. Price setting is a key factor in determining profit. Careful analysis is necessary in determining the correct pricing strategy for a company. For a company to become profitable, income must exceed expenses. Expenses can be defined as the cost of resources used in the activities of a business. • Management team Clay Craft company have a team management as a back bone built the successful company. The team management included the designer, employers, promoter and finance manager. They are part of the Clay Craft team to built the successful company. Every team have their own work, as long as they give the 100% commitment for this company.